2017
DOI: 10.1364/ome.7.002023
|View full text |Cite
|
Sign up to set email alerts
|

Tunable reflective liquid crystal terahertz waveplates

Abstract: Tunable liquid crystal devices that can change terahertz wave polarization continuously have many potential applications in terahertz optical systems. We present a reflective liquid crystal terahertz waveplate with sub-wavelength metal grating and metal ground plane electrodes. The thickness of the liquid crystal layer can be reduced to ~10% of that needed for the same phase shift at a given frequency in a transmissive waveplate. We experimentally demonstrate the same tunability as in the transmissive type jus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…In addition, the operating frequency was electrically tunable in both modes and the modulation time was at millisecond scale. Wang et al designed a reflective terahertz waveplate using metallic grating, LC and a metallic ground . It was demonstrated that the LC waveplate had considerable phase shift (1.2 π at 0.5 THz).…”
Section: Beam Steering Based On Electromagnetic Metasurfacesmentioning
confidence: 99%
“…In addition, the operating frequency was electrically tunable in both modes and the modulation time was at millisecond scale. Wang et al designed a reflective terahertz waveplate using metallic grating, LC and a metallic ground . It was demonstrated that the LC waveplate had considerable phase shift (1.2 π at 0.5 THz).…”
Section: Beam Steering Based On Electromagnetic Metasurfacesmentioning
confidence: 99%
“…In addition, in Figure 1c, a multifunctional photonic switch with a resonance response controlled both in terms of its magnitude and wavelength has been demonstrated. Other proposed applications involve electrically tunable phase modulators and polarization converters, [11,39] cloaks with the capability of real-time control of invisibility, [40] and tunable frequencyselective surfaces. [41,42] Moreover, as LCs exhibit a large anisotropy under modulation, they have been exploited in hyperbolic metamaterial implementations offering electric-field-driven toggling between elliptic and hyperbolic dispersion relations, and between normal and negative refraction.…”
Section: Liquid Crystalsmentioning
confidence: 99%
“…Liquid crystals (LCs) are good candidates for electrically manipulated active materials at THz frequencies using metallic 20 or porous graphene electrodes 21 . Thus, a reflective terahertz waveplate based on LC layers embedded with a metal wire grid is used to control the LC refractive index 20 . By tuning the applied voltage, the THz incident wave polarization can be appropriately converted.…”
Section: Introductionmentioning
confidence: 99%